2014
DOI: 10.5206/eei.v23i1.7705
|View full text |Cite
|
Sign up to set email alerts
|

Summer Learning Loss among Elementary School Children with Reading Disabilities

Abstract: This study investigated whether students with reading disabilities (RD) showed greater regression in reading skills than did non-RD students over the summer vacation. The RD group consisted of 30 students in grades 4 to 6 from a private school for students with learning disabilities and a comparison group of 30 average readers in grades 4 to 6 attending a public school. All students were tested in May/June and September on measures of reading achievement, phonological processing, and oral receptive vocabulary.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
0
18
0
2
Order By: Relevance
“…Other nonmalleable variables such as race and ethnicity and English language learning would also appear to be related to the summer regression in academic achievement, with students from non-White backgrounds being more likely to experience summer slide without readily recouping (Ford & Moore, 2013; Kim, 2004). The presence of a disability does appear to increase the likelihood and degree of summer regression in academic achievement with lower levels of recoupment (Barton & Coley, 2009; Gershenson & Hayes, 2017; Menard & Wilson, 2014). Both research and case law appear to support the need for ESY services for some students with IEPs.…”
mentioning
confidence: 99%
“…Other nonmalleable variables such as race and ethnicity and English language learning would also appear to be related to the summer regression in academic achievement, with students from non-White backgrounds being more likely to experience summer slide without readily recouping (Ford & Moore, 2013; Kim, 2004). The presence of a disability does appear to increase the likelihood and degree of summer regression in academic achievement with lower levels of recoupment (Barton & Coley, 2009; Gershenson & Hayes, 2017; Menard & Wilson, 2014). Both research and case law appear to support the need for ESY services for some students with IEPs.…”
mentioning
confidence: 99%
“…If, in fact, students suffer significant skill loss during shorter breaks, the way the current school calendar is set with a winter break, a spring break, and a longer summer break creates potential for a decline in students' reading skills two to three times per year. This potential could be even more pressing for the reading achievement of students receiving special education services because of the amount of time it may take to recoup those skills, and due to the compounding effect the loss of reading skills can have for students with reading disabilities (Menard & Wilson, 2014). A review of data in the district where the current study was conducted revealed that during the school year prior to this study (2017)(2018) 67% of the second through sixth grade students who participated in the current study demonstrated reading loss after the school's winter break.…”
Section: Problem Statementmentioning
confidence: 99%
“…Many studies have documented the detrimental effects that a long break from school, such as summer break, can have on school achievement Allington, McGill-Franzen, Camilli, Williams, Graff, Zeig, Zmach, & Nowak, 2010;Cooper, Nye, Charlton, Lindsay, & Greathouse, 1996;Heyns, 1978;Phillips & Chin, 2004). The loss of reading skills that can happen over breaks from school may have a compounding effect over multiple summers, particularly for students with reading disabilities (Menard & Wilson, 2014). Menard and Wilson (2014) addressed the compounding effect that summer reading loss can have on students with reading disabilities (RD), and noted that the effects are likely to grow over multiple summers.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
See 2 more Smart Citations